Architectural History in India (Qutb Minar Mosque as a Case Study) - سلوم, صابر محمود; عود, معتصم مالك; الجبوري, ابراهيم حسين (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
I was chosen for my research tagged (architectural history in India, the Power of Islam Mosque as a model) in Delhi because of the importance of this mosque in the minds of Muslims and Hindus alike and in order to study an important architectural aspect of our Islamic human heritage that is absent from the minds of researchers, especially Muslims, which need specialized scientific studies that highlight Revealing the art of architecture among Muslims during the twelfth century AD, which was not purely Islamic, but the local Indian artistic heritage had a great role in crystallizing the ideas of the architects who built this mosque and were inspired by some local artistic and architectural elements such as the sacred lotus flower, as well as the cupolas with human forms in raising The domes of the mosque.This study was the result of the field visit that we made to this mosque, and it was studied thoroughly by taking measurements of the mosque and its architectural elements, preceded by a historical study on the emergence of the first mosques in India, the historical events associated with them, and the origins of some local architectural elements, as well as the decorative formations and their mutual influences between the central regions of Asia. And the Indian subcontinent, as well as my reliance on foreign and Arab references in writing this research. I also dealt in this study with the layout and architecture of the mosque and the most important increases that occurred to it during the reign of Qutb al-Din Aibak and the Mamluk Sultan al-Tamash and his successor, Ala al-Din al-Khilji, and I reinforced my research with a group of paintings and pictures about this mosque Wonderful. And from God is success